PENGEMBANGAN SOSIAL, BUDAYA DAN EKONOMI MASYARAKAT KOLONISASI SUKADANA TAHUN 1935-1942 - Kirana Dea Fahira; Elis Setiawati (Swarnadwipa, 2020)
The problem in this study is to analyze the social, cultural and economic development of the Sukadana colonization community. The purpose of this study is to analyze and describe developments in the social, cultural and economic fields and their impacts. The research method uses the historical method which is a study of various sources containing information about the past and is carried out systematically, research results, the role of the Dutch East Indies government in conducting the Colonization program in Sukadana with various systems for the success of this program. The government initially financed the entire Colonization program by providing land as a place to live and farm, then rice seeds and agricultural tools, then the government also established a debt system to banks so that the Colonists could not pay because the interest was increasing every year until the bank was finally closed. Until the condition of the Colonists improved every year and they could finance their own livelihood so that the government no longer provided assistance. Until 1941 the capital city of Sukadana, namely Metro, had become the seat of a Controller, Engineer, and Government Doctor. Metro City also has a large market, Post Of ice, Pesanggrahan, Mosque, and electric lighting.